APPLICATION OF SOLAR CELL TECHNOLOGY AS A SOURCE OF ENERGY LIGHTING TOOLS FOR CATCHING FISH IN STOOD CAGES - Sunarsono, Hery; Rahman, Taufiq; Mardiansyah, Yopy; Handayani, Vitri Aprilla (Fakultas Teknik, Universitas Riau Kepulauan, 2023)
The method of catching fish carried out by traditional fishermen in